0530 Adherence to Positive Airway Pressure (PAP) devices: Feasibility of a Web-based Self Management Program. (12th April 2019) - Dickerson, Suzanne S; TenBrock, Eric; Smith, Patrica; KWon, Misol; Chacko, Thomas; Li, Chin-Shang; Dean, Grace E
Abstract: Introduction: To support PAP adherence, a comprehensive and accessible self-management program is needed in the primary care setting to promote living with and adjusting to PAP treatment of obstructive sleep apnea (OSA). This study tested the usability and feasibility of a web-based program to support self- management, provider communication and motivation for individuals beginning PAP treatment. Methods: A mixed-method approach was used to follow a sample of 20 newly diagnosed patients with OSA (Apnea/Hypopnea Index (AHI) of >10 and <5 central events/ hr.) who are beginning PAP treatment. After 1 week, the treatment group participants were interviewed by telephone to determine usability. The outcome was (% days of use >4 hours per night) at 1 month, accessed from PAP compliance reports. Analysis compared treatment group and standard care control group outcomes using Wilcoxon Rank-Sum test. A standard care group was matched for age, gender and severity. Results: Among 20 participants, the mean age was 48 (±11.3, median 52, range 30-61) years, 65% male, 95% white and a mean AHI of 41 (±25.6, median 29.1, range 14-85). Results indicated that compliance was 63% in the treatment group and 49% in the matched control (p= .228). Participants in the treatment group who viewed the website (n=14) had 80% compliance and those who did not participate (n=6) had 23% compliance (p=.005). Average minutes using the website was 71.6 (±73, median 48, range 2-244). Participants reported that the website provided comprehensive, focused, well-organized information and useful tools to monitor their progress, and trouble-shoot their issues. Participants commented that on the website, users 'stories helped them understand how long it would take to feel better and adjust to using the PAP. Breathe2Sleep™ website provided comprehensive and focused content that motivated their self-management. Conclusion: The Self-Management Program Website was useful in promoting adherence to PAP in newly diagnosed participants and would be a cost effective way to provide self-care information and tools to encourage patient engagement to improve adherence. Support (If Any): The Patrica Garman Fund, School of Nursing, University at Buffalo.